1974
DOI: 10.1161/01.str.5.6.707
|View full text |Cite
|
Sign up to set email alerts
|

To-and-Fro Movement and External Escape of Carotid Arterial Blood in Brain Death Cases. A Doppler Ultrasonic Study

Abstract: Abstract:To • In brain death cases who showed nonfilling phenomena in the internal carotid angiograms, the blood flow velocity patterns of the common carotid arteries were characterized by involvement of a single systolic peak and a marked reverse flow component which had never been observed in healthy subjects.The individuality of each blood flow velocity pattern in the common, internal and external carotid arteries was made clear by placing the transducer in contact with the respective artery in a certain ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…During the years since that report, additional confirmatory tests have been introduced in the medical literature 11,[16][17][18][19][20][21][22][23] (table 1), and a picture has emerged that reliable tests are available. The tests can be divided into those that evaluate electrical function and those that assess blood flow.…”
Section: Where Did the Confirmatory Testsmentioning
confidence: 99%
“…During the years since that report, additional confirmatory tests have been introduced in the medical literature 11,[16][17][18][19][20][21][22][23] (table 1), and a picture has emerged that reliable tests are available. The tests can be divided into those that evaluate electrical function and those that assess blood flow.…”
Section: Where Did the Confirmatory Testsmentioning
confidence: 99%
“…It has been demonstrated that the insonation of the ICA at the level of the siphon and at the extracranial level, through transorbital and cervical insonation, may show a sonographic pattern of circulatory arrest [39,40]. This gives evidence for the absence of flow in the whole anterior cerebral circulation, even in case of lack of temporal windows.…”
Section: Discussionmentioning
confidence: 99%
“…76 Transcranial Doppler is a validated confirmatory test, with sensitivity varying from 91% to 99% and a specificity of 100%. [77][78][79][80][81][82][83][84][85][86][87][88] A portable Doppler device is used with insonating of both middle cerebral arteries through the temporal bone above the zygomatic arch. The posterior circulation should be insonated, but the distal basilar artery cannot be reliably seen.…”
Section: Insertion Of Oxygen Catheter and Observing Possible Breathingmentioning
confidence: 99%